Effect of Theobromine Consumption on Serum Lipoprotein Profiles in Apparently Healthy Humans with Low HDL-Cholesterol Concentrations - Jacobs, Doris M.; Smolders, Lotte; Lin, Yuguang; de Roo, Niels; Trautwein, Elke A.; van Duynhoven, John; Mensink, Ronald P.; Plat, Jogchum; Mihaleva, Velitchka V. (Frontiers in Molecular Biosciences, 2017)
Scope: Theobromine is a major active compound in cocoa with allegedly beneficial effect on high-density-lipoprotein-cholesterol (HDL-CH). We have investigated the effect of theobromine (TB) consumption on the concentrations of triglyceride (TG) and cholesterol (CH) in various lipoprotein (LP) subclasses. Methods: In a randomized, double-blind, placebo-controlled, cross-over study, 44 apparently healthy women and men (age: 60+/-6 years, BMI: 29+/-3 kg/m2) with low baseline HDL-CH concentrations consumed a drink supplemented with 500 mg/d theobromine for 4 weeks. TG and CH concentrations in 15 LP subclasses were predicted from diffusion-edited 1H NMR spectra of fasting serum. Results: The LP phenotype of the subjects was characterized by low CH concentrations in the large HDL particles and high TG concentrations in large VLDL and chylomicron particles, which clearly differed from a LP phenotype of subjects with normal HDL-CH. TB only reduced CH concentrations in the LDL particles by 3.64 and 6.79%, but had no effect on TG and CH in any of the HDL, VLDL and CM subclasses. Conclusion: TB was not effective on HDL-CH in subjects with LP phenotype characterized by low HDL-CH and high TG in VLDL.